Structural and Functional Characterization of an Influenza Virus RNA Polymerase-Genomic RNA Complex - Resa-Infante, Patricia (American Society for Microbiology (ASM), 2010)
The replication and transcription of influenza A virus are carried out by ribonucleoproteins (RNPs) containing each genomic RNA segment associated with nucleoprotein monomers and the heterotrimeric polymerase complex. These RNPs are responsible for virus transcription and replication in the infected cell nucleus. Here we have expressed, purified, and analyzed, structurally and functionally, for the first time, polymerase-RNA template complexes obtained after replication in vivo. These complexes were generated by the cotransfection of plasmids expressing the polymerase subunits and a genomic plasmid expressing a minimal template of positive or negative polarity. Their generation in vivo was strictly dependent on the polymerase activity; they contained mainly negative-polarity viral RNA (vRNA) and could transcribe and replicate in vitro. The three-dimensional structure of the monomeric polymerase-vRNA complexes was similar to that of the RNP-associated polymerase and distinct from that of the polymerase devoid of template. These results suggest that the interaction with the template is sufficient to induce a significant conformation switch in the polymerase complex.